Agile Management in Healthcare Improving Patient Outcomes through Flexibility and Responsiveness - Saleh, Haifa Hadi; Abbas, Zeyad Ali; Latif, Nabaa; Khalil, Ziyad Tariq (Journal of Ecohumanism, 2024)
Background: The dynamic nature of healthcare environments necessitates adaptive management strategies to enhance patient outcomes. Traditional management approaches often fall short in addressing the rapidly evolving demands of healthcare settings, leading to inefficiencies and suboptimal patient care. Objective: The article aims to investigate how the application of agile management principles in healthcare environments can enhance patient outcomes by emphasizing adaptability and quick responses. It aims to comprehend the advantages and obstacles of implementing agile methodologies in clinical and administrative procedures. Methods: An extensive review of literature was carried out, examining peer-reviewed articles, case studies, and empirical research on agile management in the healthcare sector. Moreover, a set of interviews was conducted with healthcare professionals and administrators to acquire practical insights. Data from healthcare organizations using agile methods were also examined to evaluate how they affected patient results. Results: The results show that agile management greatly improves healthcare organizations’ capacity to quickly react to changes and patient demands. Significant enhancements were noted in patient contentment, decreased wait times, and overall care quality. Obstacles like reluctance to change and the necessity for ongoing training were recognized but were eased through specific actions. Conclusion: Agile management principles provide a practical answer to enhancing patient results in healthcare environments. By promoting flexibility and adaptability, healthcare institutions can improve their ability to address the ever-changing and intricate needs of patients, resulting in higher levels of satisfaction and quality of care. Additional research is advised to investigate the lasting effects and improve agile implementation approaches in various healthcare settings.